Teachers' Perspectives in Using Disney Songs in the Music Classroom. (October 2016) - Lesser, Andrew
Integrating popular music as part of the public school music curriculum has been a topic of debate among many educators and researchers. Songs from the Disney Corporation, specifically from movies, television shows, and performers specifically marketed by Disney, are particularly significant due to their widespread popularity. In this article, the author compares various perspectives of researchers and practicing teachers as to their opinions regarding the use of Disney songs in their classrooms. Specific usages and incorporation into instructional methods are described, in contrast to opinions why certain educators oppose the use of Disney music, including specific songs or Disney music as an entity.